Factors for the Implementation of Talent Management in the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia - Muammar Yuliana; Edy Sutrisno; Asropi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Implementation of effective talent management at the Ministry of Marine Affairs and Fisheries (MMAF) has an important role in optimizing talent potential and improving organizational performance. This study aims to identify and analyze the factors that influence the implementation of talent management in MMAF focusing on the marine and fisheries sector in Indonesia. The research method used is a qualitative approach by conducting in-depth interviews with high-ranking officials, administrators, and functional officials who are directly involved in managing talent management at the Ministry. The results of the study found that the factors that influence the implementation of talent management in MMAF are (1) top management's commitment to talent management plays an important role in creating an environment that supports effective talent management, (2) clear policies and procedures in talent management facilitate the implementation and monitoring of these programs, (3) structured career development and learning opportunities help motivate employees to work better and stay in the organization and (4) proper rewards and recognition for employee achievements and contributions can increase job satisfaction and talent retention. This research provides recommendations to the Ministry to develop competitive strategies to attract, develop and retain quality talent.